Perancangan Sistem Informasi Rekam Medis Elektronik pada Pelaporan Indeks Penyakit Poli Jantung dengan Metode Waterfall - Aisyah, Syllah; Sufyana, Candra Mecca; Suryani, Ade Irma (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Through conducted research, it has been found that X Hospital in Bandung City has a computerized disease index reporting system. However, the data input still relies on manual input into Microsoft Excel by entering data one by one, which can result in data inconsistencies thus causing delays in generating disease index data report including those for the cardiology department. Therefore, there is a need for an electronic medical record information system for reporting heart disease indices, utilizing visual studio 2010 programming language and Microsoft access as the database. The objective is to facilitate staff in generating disease index reports and ensure the efectiviness and efficiency of the generated reports. To achieve this goal, the waterfall development method is employed, applying a sequential approach in software development from planning to structured and phased system testing. During this process, data is collected through qualitative data analysis with a descriptive approach, enabling a deeper understanding of the issues, exploration of user needs, and obtaining insights necessary for designing the system effectively. The application of this method result in an integrated disease index system that enhances efficiency and accurancy in reporting heart disease indexes, while reducing the risk of errors and delays in report generation.